ESTRUS AND OVULATION INDUCTION OF POSTPARTUM LACTATING ONGOLE COWS WITH STEROIDS, GONADOTROPINS AND PROSTAGLANDIN - NAIDU, G VENKATA; RAO, A SESHAGIRI; NAIDU, K VENUGOPAL; RAO, K BABU (The Indian Journal of Animal Reproduction, 2023)
In the present study with a view to obviate prolonged calving interval, four estrus and ovulation induction hormonal protocols were initiated on day 45 postpartum with 20 postpartum lactating cows in each group. The cows in the treatment group 'P: (CIDf\a:t PGF 211 +EB) exhibited 100 per cent responseand ovulation with a better degree synchrony. The estrus duration was found to be significantly (P
Keywords: Estrus; Ovulation induction; Postpartum lactating Ongole (zebu) cows; Reproductive performance; EB; GnRH; PGF2alpha